Periostin: A Potential Biomarker and Therapeutic Target in Pulmonary Diseases - Nafaa Alzobaidi; Sana Rehman; Maaz Naqvi; Kavita Gulati; Arunabha Ray (Frontiers Media S.A., 2022)
Periostin is a matricellular, nonstructural protein belonging to the fasciclin family and is encoded by the POSTN gene in humans. Periostin plays an important role in maintaining a normal tissue matrix in the lungs. Despite the vital role as a structural mediator in tissue growth and repair, periostin is involved in the pathogenic mechanism during tissue remodeling and fibrosis. Periostin is a chemoattractant mediator, promotes eosinophil recruitment and adhesion on the airways sub-epithelial membrane of asthmatic patients. POSTN gene was identified as one of the highly expressed genes induced by interleukins IL-13, IL-5 and IL-4 - the key cytokines of Th2 immune responses in the bronchial tissues of asthmatic patients. This review highlights the potential role of periostin as a validated biomarker in respiratory disease progression and its candidacy to predict the response to treatments targeting Th-2 cytokines in bronchial asthma. In addition, its potential role in COPD, IPF, lung cancer and lung infection, is also speculated.   Keywords Periostin, Asthma, Pneumonia, COPD, Idiopathic pulmonary fibrosis, Biomarker